Pemanfaatan Limbah Organik dalam Pembuatan Bioinsektisda berbasis Bacillus thuringiensis sebagai Agens Pengendalian Hama Tanaman Caisim Brassica juncea - Dessy Tri Astuti; Nurhayati Damiri; Yulia Pujiastuti; Siti Rakhmi Afriani (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Astuti et al, 2018. Utilization of Organic Waste in the Making of Bacillus thuringiensis-based Bioinsecticides as Agents for Control of Caisim Brassica juncea Pests. JLSO 7(2):136-143.Â Bacillus thuringiensis was one of the entomopathogenic bacteria that can produces toxic crystal proteine (á´•-endotoksin). The use of bioinsecticide as a biological agent in pest control was one component of integrated pest control (IPM). The aimed of this reseacrh was to know the population of pests in plants and the percentage of damage to plants that exist in each treatment. The research was conducted in a vegetable garden in the Banyuasin district in November 2017 until January 2018. The research method used a randomized block design with 5 treatments and 4 blocks. The treatment was Bacillus thuringiensis KJ3R5 cultured in coconut water and rice washing waterÂ (A), Bacillus thuringiensis LC2 cultured in coconut water and tofu wastewater (B), commercial Bacillus thuringiensis (C), inorganic insecticide (sidametrin) (D), and water as control (E). The variables observed were arthropod populations on the canopy and ground surface of choy sum (Brassica rapa var. parachinensis or Brassica chinensis var. parachinensis) plants. The results showed that 4 species of pests i.e. Pyllotreta crucifera, Spodoptera litura, Plutella xylostella, and Helula sp. Treatment with Bacillus thuringiensis LC2 (B) resulted in reduction of plant damage by 61%.